Jender dan Manajemen Sekolah: Suatu Analisis Wawasan Sistem tentang Jabatan Manajerial - Nurul Ulfatin (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
Gender and School Management: An Analysis of the System of Managerial Positions. It has been necessary to study gender issues continously since women dominated schools as teachers, especially in terms of their promotion for managerial positions. The main problem of women’s promotion is on the term gender itself, which is a stereotype resulted from a ‘masculine’ culture. Men and women are then perceived differently in their managerial positions: women face more obstacles than men. Some models which can be used to explain the obstacles are women position, discrepancy, and meritocracy models, in addition to the organization structure and the psychological view. In a study, the obstacles would not be apparent unless qualitative paradigm with micro-subjective scope were utilized. Therefore, employing a case study method for investigation would make it possible to reveal the obstacles faced by women more comprehensively.